ОСОБЕННОСТИ ЛАТИНСКОГО ЯЗЫКА - Олимбоева Донахон Абдувалиевна Мухамедова Матлуба Сатвалиевна (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
Teaching Latin in medical universities is the issue of particular importance. This article discusses the positive results of studying proverbs and aphorisms along with the study of medical terms in Latin classes.